Response of rigid and flexible buildings in an earthquake - Lapin V. A.; Shokhbarov Y. M.; Aldakhov Y. S.; Omarov Zh. A. (BIO Web of Conferences)
During the earthquake on March 26, 2018 with a source in the Almaty region, the stations of the engineering and seismometric service received instrumental records on buildings with various design solutions. The article discusses instrumental records (accelerograms) recorded on a four-storey frame building and an 11-storey building with a steel frame. Spectral curves were plotted at the registration points on the roof and basement parts of buildings. It was found that the periods of the prevailing fluctuations of the base of the structure are 0.16-0.21 sec for the two indicated buildings. The spectral curves at the basement level have the same shape. Instrumental records are included in the database of accelerograms of KazRDICA JSC.